2013
DOI: 10.1007/s00216-013-7237-y
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of diosmetin 3-O-glucuronide as major metabolite of diosmin in humans, using micro-liquid-chromatography–mass spectrometry and ion mobility mass spectrometry

Abstract: Diosmin is a flavonoid often administered in the treatment of chronic venous insufficiency, hemorrhoids, and related affections. Diosmin is rapidly hydrolized in the intestine to its aglicone, diosmetin, which is further metabolized to conjugates. In this study, the development and validations of three new methods for the determination of diosmetin, free and after enzymatic deconjugation, and of its potential glucuronide metabolites, diosmetin-3-O-glucuronide, diosmetin-7-O-glucuronide, and diosmetin-3,7-O-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…Dio-39-G, the major form of diosmetin that circulates in human plasma, has been reported previously (Silvestro et al, 2013), but little is known of chrysoeriol metabolism. In our study, Chr-49-G and Dio-39-G exhibited higher plasma exposure than Chr-7-G and Dio-7-G (P , 0.05) after oral administration of luteolin in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Dio-39-G, the major form of diosmetin that circulates in human plasma, has been reported previously (Silvestro et al, 2013), but little is known of chrysoeriol metabolism. In our study, Chr-49-G and Dio-39-G exhibited higher plasma exposure than Chr-7-G and Dio-7-G (P , 0.05) after oral administration of luteolin in rats.…”
Section: Discussionmentioning
confidence: 98%
“…After oral administration, intestinal microflora enzymes rapidly hydrolyze diosmin into its aglycone, diosmetin, which is then absorbed through the intestinal wall. At systemic circulation level, diosmetin is enzymatically esterified to its relevant metabolite, 3-O-glucuronide, which is further esterified into 3,7-di-O-glucuronide [47,48]. Experimental evidence has shown that diosmin has the ability to inhibit P-glycoprotein [45] and several cytochrome P450 (CYP) enzyme isoforms (CYP1A1, CYP1A2, CYP2B1, CYP2C8, CYP2C9, CYP2D6, CYP2E1, CYP3A4, and CYP3A5).…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
“…In comparison, the quercetin molecule contains five hydroxyl groups without any methoxy group (Figure 1). Pharmacokinetic studies demonstrated that diosmin was rapidly absorbed, followed by hydrolysis through intestinal enzymes to release the aglycone diosmetin after an oral administration of diosmin (Cova et al, 1992;Silvestro et al, 2013). Diosmetin is then rapidly absorbed with a half-life in plasma ranging from 26 to 43 hours in humans (Cova et al, 1992).…”
Section: Diosmin and Diosmetinmentioning
confidence: 99%
“…After intestinal absorption and biotransformation, metabolites are eliminated in the urine, mainly as glucuronic acid conjugates. Diosmetin-3-Oglucuronide was identified as the major circulating metabolite of diosmetin in plasma and in urine (Silvestro et al, 2013).…”
Section: Diosmin and Diosmetinmentioning
confidence: 99%